THE OTHER SIDES OF PESANTREN: MAGICAL PRACTICES AROUND PESANTREN IN BANTEN - Fahmi Irfani; Azkia Muharom Albantani; Ahmad Suhendra; Hafizhah Masnin (Akademika : Jurnal Pemikiran Islam, 2021)
Pesantren in Banten have different characteristics compare to other pesantren in Indonesia. Discussing about this Province, most people believe that Banten is of a Province in Indonesia which is famous with its Ulama, Kyai, Santri and Pesantren. This research discusses about practices of magical culture in Pesantren around Banten. The research model used in this study is qualitative-descriptive. Historical studies are used to present a narrative and chronological presentation of the storyline of a discussion. Results showed that stereotypes and beliefs arise because Islamic values have traditionally been rooted in most Banten citizens, culturally and ritually. One of the characteristic of Pesantren in Banten is that every santri are taught with magic, silat and tasawuf knowledge. Those are characteristics that have always been a matter of discussion, people believe that there are practices of magic in every pesantren in Banten. Some sources call Banten a center for the occult sciences, as well as being known as a religious area. Magical practice is still considered important for the people of Banten, especially those living in rural areas to solve practical problems in their social life. In addition, the existence of jawara and pesantren has created its own cult which is somewhat different from the dominant culture of Banten society